Acid-sensitive ion channel 1a regulates TNF-α expression in LPS-induced acute lung injury via ERS-CHOP-C/EBPα signaling pathway. (January 2023) - Liu, Yanyi; Zhu, Yueqin; Wang, Lili; Li, Kuayue; Du, Na; Pan, Xuesheng; Li, Yangyang; Cao, Rui; Li, Bowen; Lin, Huimin; Song, Yonghu; Zhang, Yunting; et al.
Abstract: Background: Acute lung injury (ALI) is the local inflammatory response of the lungs involved in a variety of inflammatory cells. Macrophages are immune cells and inflammatory cells widely distributed in the body. Acid-sensitive ion channel 1a (ASIC1a) is involved in the occurrence of ALI, but the mechanism is still unclear. Methods: Kunming mouse were stimulated by Lipopolysaccharides (LPS) to establish ALI model in vivo, and RAW264.7 cells were stimulated by LPS to establish inflammatory model in vitro. Amiloride was used as a blocker of ASIC1a to treat mice, and dexamethasone was used as a positive drug for ALI. After blockers and RNAi blocked or silenced the expression of ASIC1a, the expressions of ASIC1a, endoplasmic reticulum-related proteins GRP78, CHOP, C/EBPα and TNF-α were detected. The Ca 2+ concentration was measured by a laser confocal microscope. The interaction between CHOP and C/EBPα and the effect of C/EBPα on the activity of TNF-α promoter were detected by immunoprecipitation and luciferase reporter. Results: The expressions of ASIC1a and TNF-α were increased significantly in LPS group. After the blocker and RNAi blocked or silenced ASIC1a, the expressions of TNF-α, GRP78, CHOP were reduced, and the intracellular Ca 2+ influx was weakened. The results of immunoprecipitation showed that CHOP and C/EBPα interacted in the macrophages. After silencing CHOP, C/EBPα expression was increased, and TNF-α expression was decreased. The results of the luciferase reporter indicated that C/EBPα directly binds to TNF-α. Conclusion: ASIC1a regulates the expression of TNF-α in LPS-induced acute lung injury via ERS-CHOP-C/EBPα signaling pathway. Graphical Abstract: ga1 Highlights: The increase of ASIC1a can activate ERS and increase CHOP expression. ASIC1a can regulate the expression of TNF-α in LPS-induced acute lung injury. Blocking ASIC1a can reduce inflammation and lung damage by ERS-CHOP-C/EBPα pathway.